2019
DOI: 10.1016/j.bbmt.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

High Graft-versus-Host Disease-Free, Relapse/Rejection-Free Survival and Similar Outcome of Related and Unrelated Allogeneic Stem Cell Transplantation for Aplastic Anemia: A Nationwide Swedish Cohort Study

Abstract: Background and aims. Aplastic anemia (AA) is a rare but life-threatening disease. The introduction of immunosuppressive treatment (IST) and hematopoietic stem cell transplantation (HSCT) has considerably improved the outcome of patients with AA. However, modern-day population-based data are limited. This thesis aimed to retrospectively analyze the incidence, treatment modalities, survival, and immune markers in the bone marrow of patients diagnosed with AA in Sweden from 2000-2011. Patients and methods. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 184 publications
1
11
0
Order By: Relevance
“…Graft failure and disease relapse are the main reasons that lead to retransplantation mentioned in a study 16 . Factors associated with graft failure include HLA incompatibility, underlying disease, type of conditioning regimen, source of CPH employed, low HPC dose, ex vivo T cell depletion, major ABO incompatibility, grafts from female donors to male recipients and disease status at the transplantation time, infection or sepsis and non-adherence to drug therapy with ursodeoxycholic acid and immunosuppressants in the post-HSCT period 17 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Graft failure and disease relapse are the main reasons that lead to retransplantation mentioned in a study 16 . Factors associated with graft failure include HLA incompatibility, underlying disease, type of conditioning regimen, source of CPH employed, low HPC dose, ex vivo T cell depletion, major ABO incompatibility, grafts from female donors to male recipients and disease status at the transplantation time, infection or sepsis and non-adherence to drug therapy with ursodeoxycholic acid and immunosuppressants in the post-HSCT period 17 .…”
Section: Discussionmentioning
confidence: 93%
“…HSCR seems a little promising approach, but there are few treatment options for relapse after the first transplant such as chemotherapy with new drugs, infusion of donor lymphocytes for allogeneic transplantation, retransplantation or a combination of them. In this context, HSCR is the treatment which favors greater OS 7 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…GRFS is a composite endpoint that is mainly used for transplants against hematological malignancies [25]. Recent studies on the outcomes of transplants for aplastic anemia also reported GRFS or GFFS, both of which were defined as the same criterion with relapse-free indicating GF-free [30][31][32][33]. A recent Korean retrospective study suggested a favorable effect of the use of ATG for GRFS only in PBSCT or mismatched donor transplant cohorts [30].…”
Section: Discussionmentioning
confidence: 99%
“…The term"GRFS"is used as a composite endpoint, focused on survival without relapse and the absence of clinically relevant GVHD, and is primarily used for malignant disorders where there is a benefit from the Blood Cell Therapy-The official journal of APBMT-AlloHCT for SAA using T-cell depletion graft-versus leukemia(GVL)effect 24 . A novel definition for GRFS, for aplastic anemia, was recently suggested to use rejection-free survival instead of relapse-free survival, maintaining the standard inclusions of grade Ⅲ-Ⅳ cGVHD and clinically significant cGVHD 25 . We proposed a modification of the original definition of GRFS to include grade Ⅱ aGVHD and mild cGVHD in nonmalignant hematological disorders, as there is no benefit from the GVL effect 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Disease monitoring GVHD-Free⊘Rejection-free survival(GRFS)was calculated in months from the date of alloHSCT to the date of the event or last follow-up whichever came first. Grades Ⅱ-Ⅳ acute GVHD, any grade of chronic GVHD, graft failure, and death were recorded as events, as SAA is a non-malignant disorder 25,26 . Long-term complications were studied through retrospective chart review.…”
Section: Graft Versus Host Disease Prophylaxismentioning
confidence: 99%